Sprachatlas des Dolomitenladinischen und angrenzender Gebiete Band 2 - Goebl, Hans (Editions de Linguistique et de Philologie, 2012)
The second volume contains 218 dialect maps which embrace dialectal terminologies from human relations to the different parts of the house.Second map volume of a linguistic atlas with five map volumes and two index volumes.